1998
DOI: 10.1001/archsurg.133.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy vs Open Cholecystectomy in the Treatment of Acute Cholecystitis

Abstract: To compare the results of laparoscopic cholecystectomy (LC) with those of open cholecystectomy (OC) in the treatment of acute cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
2
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(153 citation statements)
references
References 6 publications
15
126
2
10
Order By: Relevance
“…A case series examining patients with AC, gallbladder gangrene, hydrops and gallbladder empyema observed a conversion rate of 20.5% and a morbidity of 17% (Eldar, 1998). A retrospective case series of LC for AC found similar results to those described for cholecystolithiasis, except in operating time and conversion rate which were significantly higher (Lujan, 1995), and another larger case series described statistical diferences of conversion rate between patients with AC vs. Chronic cholecystitis (20.6% vs 4.2%) (Tan, 2006)…”
Section: (Treatment Studies 2b)mentioning
confidence: 62%
See 1 more Smart Citation
“…A case series examining patients with AC, gallbladder gangrene, hydrops and gallbladder empyema observed a conversion rate of 20.5% and a morbidity of 17% (Eldar, 1998). A retrospective case series of LC for AC found similar results to those described for cholecystolithiasis, except in operating time and conversion rate which were significantly higher (Lujan, 1995), and another larger case series described statistical diferences of conversion rate between patients with AC vs. Chronic cholecystitis (20.6% vs 4.2%) (Tan, 2006)…”
Section: (Treatment Studies 2b)mentioning
confidence: 62%
“…Low quality: it very likely that future studies change our confidence in the estimate of effect, therefore our confidence is low. Table. 2001; Elder, 1996;Finan, 2006;Zacks, 2002;Collet, 1997;Ibrahim, 2006;Weber, 2003;Feldman, 1994;Perez Lara, 2006;Sungler, 2000;Daradkeh, 1999;Ji, 2005;Fernandes, 2000;Palanivelu, 2006;da Silveira, 2006;Gurusamy, 2006;Chandler, 2000;Kiviluoto, 1998;Glavic, 2001;Eldar, 1998;Lujan, 1995;Tan, 2006;Perez-Morales, 2005;Bagia, 2001;Schafer, 2003;Kwon, 2001;Woods, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The latter underlines the need for early intervention, initiated within 72 hours after onset of symptoms. [27][28][29][30][31][32] Other proposals to decrease conversion and complication rates include percutaneous trans-hepatic gall bladder drainage followed by elective cholecystectomy 11 and laparoscopic subtotal cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic approach should initially be attempted except in cases of absolute anesthesiology contraindications or septic shock. Many prospective trials have demonstrated that the laparoscopic cholecystectomy is a safe and effective treatment for ACC [102][103][104][105][106]. A recently published meta-analysis demonstrated that laparoscopic cholecystectomy in ACC [107] is the preferred approach having lower mortality and morbidity, significantly shorter post-operative hospital stay, and reduced rate of pneumonia and wound infections, compared with the open technique.…”
Section: Statement 12mentioning
confidence: 99%